Assessment of the effects of scrape-off layer fluctuations on first wall sputtering with the TOKAM-2D turbulence code. (8th September 2016) - Marandet, Y; Nace, N; Valentinuzzi, M; Tamain, P; Bufferand, H; Ciraolo, G; Genesio, P; Mellet, N
Abstract: Plasma material interactions on the first wall of future tokamaks such as ITER and DEMO are likely to play an important role, because of turbulent radial transport. The latter results to a large extent from the radial propagation of plasma filaments through a tenuous background. In such a situation, mean field descriptions (on which transport codes rely) become questionable. First wall sputtering is of particular interest, especially in a full W machine, since it has been shown experimentally that first wall sources control core contamination. In ITER, beryllium sources will be one of the important actors in determining the fuel retention level through codeposition. In this work, we study the effect of turbulent fluctuations on mean sputtering yields and fluxes, relying on a new version of the TOKAM-2D code which includes ion temperature fluctuations. We show that fluctuations enhance sputtering at sub-threshold impact energies, by more than an order of magnitude when fluctuation levels are of order unity.